2000
DOI: 10.1192/apt.6.6.414
|View full text |Cite
|
Sign up to set email alerts
|

Running an effective community mental health team

Abstract: Community psychiatric teams are an integral part of modern mental health services. The development of such teams has allowed the care of patients to be transferred from institutions to the community. A Cochrane review of community-based programmes showed that community team-based psychiatric services led to a reduction in suicide rates, improved patient engagement and were more acceptable to patients (Tyrer et al, 1999). Community care also reduces the number of days patients stay in hospital, but not the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 21 publications
(20 reference statements)
4
29
0
Order By: Relevance
“…A key issue for CMHTs, therefore, is how they gate-keep access to their service [12]. Previous studies have suggested that gate-keeping decisions have been largely determined by individual clinicians and teams, rather than through formal strategic control [13].…”
Section: Introductionmentioning
confidence: 99%
“…A key issue for CMHTs, therefore, is how they gate-keep access to their service [12]. Previous studies have suggested that gate-keeping decisions have been largely determined by individual clinicians and teams, rather than through formal strategic control [13].…”
Section: Introductionmentioning
confidence: 99%
“…69 Lack of throughput can result from members' retaining, and failing to discharge, their fixed case-loads of chronic, stable and familiar cases, and their reluctance to take on potentially complex cases. 32 This again underlines the need for teams to stay outward looking, continually fostering links with other more socially inclusive forms of support. Excessive workloads can also predispose to generic monitoring and support, thus rendering team members' specialist skill-sets redundant.…”
Section: Episodic Closurementioning
confidence: 99%
“…32 While diversity within teams is to be prized, such conflicts are probably self-indulgent. Service user need requires models that encompass a wide variety of approaches and that, most importantly, have explanatory (rather than merely descriptive) power for users and their supports.…”
Section: Models Of Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of care model is often hotly contested among team members from differing disciplines who may compete to assert the primacy of their preferred model and the superiority of their associated interventions (Singh 2000). However, this competition and subsequent choosing of a particular 'professional' model (e.g., the biopsychosocial model) (Clare 1976) is time poorly spent, as it does not satisfy the diverse needs of service users (Byrne & Onyett 2010).…”
Section: Team Environment Factorsmentioning
confidence: 99%